Antifeedaant Compound From Daruju Leaves (Acanthus Ilicifolius Linn) Against Eggplant Leaves Beetle (Epilachna Sparsa) - Ade Mariadi; Ari Widiyantoro; Endah Sayekti (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2022)
Daruju (Acanthus ilicifolius Linn) contain flavonoids, terpenoids, steroids, saponins, alkaloids and tannins that can be used as antifeedant compounds. The purpose of this study is to identify the active compound antifeedant from daruju leaves against the eggplant leaf beetle (Epilachna sparsa). The antifeedant activity test was carried out on the methanol extract, the partitioned fraction and the isolate. This study was began by maceration of daruju leaf powder (1000 g) with methanol that obtained methanol extract of 130.3 g. The methanol extracts were then separated by partitioning that obtained n-hexane, dichloromethane, ethyl acetate and methanol fraction. Antifeedant activity test against eggplant leaf beetle (Epilachna sparsa) showed the dichlormethane fraction at a concentration of 6 ppm had the best activity compared to other fractions with an activity of 90.62%. Separation and purification of the dichloromethane fraction to obtain isolation was carried out by column chromatography. The isolate showed 96.1% antifeedant activity at a concentration of 6 ppm. Based on 1H-NMR spectrum showed isolate is p-Oxy-2-ethylhexyl benzaldehyde.